2020
DOI: 10.1016/j.mehy.2020.110320
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 cell entry receptor ACE2 mediated endothelial dysfunction leads to vascular thrombosis in COVID-19 patients

Abstract: Several studies have described unusually high incidence of vascular thrombosis in coronavirus disease-2019 (COVID-19) patients. Pathogenesis of the vascular thrombosis in COVID-19 is least understood for now and presents a challenge to the treating physicians. Severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2), the causative pathogen for COVID-19, has been shown to bind to angiotensin converting enzyme 2 (ACE2) protein in human epithelial cells which facilitates its entry in the organ and mediate tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
15

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(90 citation statements)
references
References 38 publications
2
73
0
15
Order By: Relevance
“…Since ACE2 is an analogue of ACE, which is a key regulator of the RAS system regulating hemodynamic homeostasis in the body, a balanced ACE/ACE2 ratio is fundamental for maintenance of endothelial integrity in vessels [65]. On the contrary, dysregulation of this ratio could be associated with vascular thrombosis [66,67]. This hypothesis is confirmed by in vitro studies carried out on lung tissues infected with SARS-CoV.…”
Section: Molecular Mechanisms Of Ace-2-covid 19 Interactionmentioning
confidence: 79%
“…Since ACE2 is an analogue of ACE, which is a key regulator of the RAS system regulating hemodynamic homeostasis in the body, a balanced ACE/ACE2 ratio is fundamental for maintenance of endothelial integrity in vessels [65]. On the contrary, dysregulation of this ratio could be associated with vascular thrombosis [66,67]. This hypothesis is confirmed by in vitro studies carried out on lung tissues infected with SARS-CoV.…”
Section: Molecular Mechanisms Of Ace-2-covid 19 Interactionmentioning
confidence: 79%
“…Recently some studies have reported complement system mediation of clotting in COVID-19 patients. Whether there is any SARS-CoV-2 specific virulence factor involved in increased thrombosis is not clear yet, however many authors have proposed a SARS-CoV-2 cell entry receptor ACE2 based mediation of vascular thrombosis [67,68]. ACE2 is known to express in human vascular endothelium and it has a well-established role in hemostasis [3,67,68].…”
Section: Immunological Bases Of Thrombotic and Neurological Symptomsmentioning
confidence: 99%
“…Whether there is any SARS-CoV-2 specific virulence factor involved in increased thrombosis is not clear yet, however many authors have proposed a SARS-CoV-2 cell entry receptor ACE2 based mediation of vascular thrombosis [67,68]. ACE2 is known to express in human vascular endothelium and it has a well-established role in hemostasis [3,67,68]. There is a plausibility that virus mediated downregulation of ACE2 signaling may induce prothrombosis [67,68], however, any concrete evidence in reference of COVID-19 is currently lacking in literature.…”
Section: Immunological Bases Of Thrombotic and Neurological Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amidst the wide range of challenges posed by COVID-19 associated thrombosis, the Kumar et al proposition of severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) cellular entry based angiotensin converting enzyme 2 (ACE2) signalling alterations being at the cornerstone of endothelial dysfunction and vascular pro-thrombotic environment, can have potentially important therapeutic implications [1] , [2] . Taking account of their molecular level description, we wish to highlight a few points to substantiate the clinical perspective of the discussion.…”
mentioning
confidence: 99%